Comparative Levels of Excessive Daytime Sleepiness in Common Medical Disorders - Stroe, Alice F (2010)
INTRODUCTION: Sleep restriction and sleep disorders are common causes of excessive daytime sleepiness (EDS). Medical disorders (MD) can also cause EDS, but previous studies have used non-standardized measures, selected samples, or have examined EDS in singular disorders. This study describes the relative degree of EDS associated with medical disorders to provide comparative data across a range of common medical conditions in a large unselected community-based sample. METHODS: Responses of 2612 individuals (aged 18-65) were assessed after excluding those with suspected sleep disordered breathing, narcolepsy, and shift workers. Participants across a range of medical disorders were evaluated using the Epworth Sleepiness Scale (ESS) and patient reports of nocturnal sleep. RESULTS: Sixty-seven percent of the sample reported a MD. The prevalence of EDS (ESS ≥ 10) was 31.4% in individuals with MD and increased as a function of number of MD (0 MD = 29.4%, 1 MD = 28.4%, 2 MD = 31.0%, 3 MD = 35.3%, 4 MD = 38.4%). Disorders which were independent predictors of EDS were ulcers OR = 2.21 (95% CI = 1.35 - 3.61), migraines OR = 1.36 (95% CI = 1.08 – 1.72), and depression OR = 1.46 (95% CI = 1.16 – 1.83) after controlling for other conditions, age, gender, time in bed, caffeine, smoking and alcohol use. Participants with ulcers had the highest prevalence of sleepiness, 50.0%, as well as the highest level of problems falling asleep (40.8%) and awakenings during the night (62.5%). CONCLUSIONS: Individuals with ulcers, migraines, and depression have independent and clinically significant levels of EDS relative to other common MD.